2003
DOI: 10.1021/jp0271559
|View full text |Cite
|
Sign up to set email alerts
|

Solute Dependence of Three Pulse Photon Echo Peak Shift Measurements in Methanol Solution

Abstract: Three pulse photon echo peak shift (3PEPS) measurement has recently become a popular method to study solvation and protein dynamics. In this paper, dependence of the 3PEPS signal on probe solute molecules was studied using several xanthene dyes and styryl dye molecules in methanol and compared with pumpprobe measurements. For xanthene dyes, the decay was faster when the blue side of the absorption spectrum was excited. This effect is considered to be the result of a limited observation window and vibrational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 74 publications
6
38
0
Order By: Relevance
“…However, as mentioned earlier, experiments have shown that solvent motions ∼10 ps, as well as a static component (i.e. ≫100 ps), are needed to fully describe solvation dynamics in methanol 31. We have evaluated trajectory length dependence for all of the model chemistries out to 25 ps, for CIS/STO‐3G out to 100 ps, and for ZINDO/s out to 300 ps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as mentioned earlier, experiments have shown that solvent motions ∼10 ps, as well as a static component (i.e. ≫100 ps), are needed to fully describe solvation dynamics in methanol 31. We have evaluated trajectory length dependence for all of the model chemistries out to 25 ps, for CIS/STO‐3G out to 100 ps, and for ZINDO/s out to 300 ps.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have suggested long‐timescale dynamics of 8.4 ± 1.6 ps for Ox4 in methanol as well as a significant static (≫ 100 ps) component 31. Thus, as with any discrete solvation model, achieving a truly ergodic ensemble of configurations is extremely challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,29,30 As pathways resulting from ESA enter the total response function with a negative signsopposite to ground-state absorption and stimulated emission pathways, which are associated with a positive sign 17 s interference between different contributions can lead to increasing TG and three-pulse photon-echo signals. 11,[29][30][31]58 The double-sided Feynman diagrams that contribute to the excitedstate isomerization signal of 1122C are schematically presented in Figure 2. Diagrams (i) and (ii) are identical to those expected for a simple two-level system.…”
Section: Methodsmentioning
confidence: 99%
“…It is also known that the echo peak shift depends on excitation wavelength. 25,26,58 To extract all of the information embraced in the signal, the echo intensity should be carefully monitored as a two-dimensional function of τ and T. Here we report two-dimensional measurements of the integrated three pulse photon echo signal by controlling the first and the second time periods, τ and T, and integrating the echo signal over the third period, τ′. The sample we have measured is a Nile blue doped poly(methyl methacrylate) (NB/PMMA) film.…”
Section: Introductionmentioning
confidence: 99%